Konsep I’jaz Dalam Persfektif Ilmu Qur’an - Ahmad Haidir; Abu Anwar (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2022)
Proverbs of the Qur'an are very important to be studied and understood in more depth because as an effort to understand or react to the supernatural to conclude the verses of the Qur'an which have words in each sentence that are very beautiful but have meaning. which is very deep, beautiful and sturdy, which encourages every human being to do everything according to his interests and desires. Amtsal also provides advice and warnings to humans, so Amtsal has a very important role in education because actually education itself contains advice and warnings in every implementation.